Sedentary behaviour and their association with academic performance among high school students in South Tamil Nadu - Manohar, Madhumitha; Uma, Sureshbalan Kumarasamy; Rajendran, Judith (International Journal Of Community Medicine And Public Health, 2019)
Background: Sedentary behaviour refers to activities that require very low energy expenditure where sitting or lying is the dominant posture. It is reported that children spend approximately 80% of their day in sedentary behaviours. It is an important risk factor for physical, psychological and socio-emotional health among school children. Epidemiological studies have shown that spending excessive time in sedentary behaviors have a negative impact on academic performance. The objectives of this study were to study the proportion of sedentary behaviours among high school students. To find out whether any association exist between sedentary behaviors with academic performance. Methods: A cross sectional study conducted from July to September, 2018 among high school students in a government school, Kanyakumari district. 213 students from class 9th and 10th standard participated in our study. Permission was obtained from school authorities after explaining the purpose of study. Data was collected using a pre tested questionnaire. Study variables included internet usage, watching television, duration of sleep, physical activity and academic performance. Data was entered in MS-Excel, analyzed for proportions, chi-square using SPSS version 16.0. Results: 61% watched TV more than 2 hours a day. 59.6% of the students spend >2 hours a day for internet browsing. 60% of the students spend <30 minutes a day for doing exercise. 45% of the students reported sleeping for 8 to 10 hours. Internet browsing and watching TV have shown significant association with academic performance. Conclusions: Sedentary behaviours are on the rise among school children. Multi component school-based interventions are necessary to minimize sedentary behaviours among school children.